SCREENING, SYNTHESIS AND CHARACTERIZATION OF BIODEGRADABLE IONIC LIQUIDS FOR ENHANCED SOLUBILITY OF SPARINGLY SOLUBLE DRUGS - LOTFI, MEYSAM (2017)
In the pharmaceutical industries and in modern medicine, it is well known that many promising drugs that are sparingly soluble in conventional solvents never enter a formulation stage due to their poor solubility as well as difficulties in delivery. In an effort to overcome this limitation, ionic liquids (ILs) as a new class of solvents, were used to enhance the solubility of two sparingly soluble drugs, Acyclovir (ACV) and Methotrexate (MTX). Due to theoretical availability of enormous ILs, COSMO-RS as a physically well-established model was used to screen the solubility of drug molecules in ILs and investigate possible solvation interactions between drugs and ILs. With regard to COSMO-RS predictions, five ILs were selected. Diethylammonium acetate, triethylammonium acetate, tributylmethylphosphonium methylsulfate, choline acetate were successfully synthesized and characterized and 1-ethyl-3-methylimidazolium acetate was commercially available. Predicted solubility results were validated experimentally and a good agreement was observed between experimental and predicted results. ILs tested in this work, showed higher solubility for ACV and MTX in comparison to available conventional solvents. Closed bottle test was performed on selected ILs to comprehend the biodegradability of ILs, which resulted in three readily biodegradable ILs.